Soft shadows using sp-line approximation - Kolivand, Hoshang (Penerbit UTM Press, 2015)
Realistic soft shadows are an important factor to enhance the realism of Augmented Reality systems. Without shadows, virtual objects would look floating over the scene resulting unrealistic rendering of AR environment. Little attention has been directed towards balanced trade-off between shadow quality and computational cost. In this study, a new approach is proposed; Quadratic Sp-line Interpolation (QSI) to soften the outline of the shadow. QSI estimates the border of hard shadow samples. In more details, a reflective hemisphere is used to capture real light then to create an environment map. Implementation of the Median Cut algorithm is performed to locate the direction of real light sources on the environment map. Subsequently, the original hard shadows are retrieved and a sample of multilayer hard shadows is produced. The proposed technique is tested by using three samples of multilayer hard shadows with a varied number of light sources that are generated from the Median Cut algorithm. The experimental results show that the proposed technique has successfully produced realistic soft shadows with low computational costs.